Effect of Rice Bran and Leucaena Supplementation on the Growth Performance of Goats Fed with Urea Treated Rice Straw - Upreti, Chet Raj; Orden, Edgar A. (Nepal Journal of Science and Technology, 2010)
An experiment was conducted for 90 days to determine the effect of energy level using different levels of RB on the UTRS as a basal diet supplemented with fixed level of Leucaena on growing goats. Experimental diets included four levels of rice bran: 0% rice bran (RB), 10% RB, 20% RB, and 30% RB in basal diets. A total of 20 growing female goats of 5 to 6 months age were randomly allocated into four different dietary groups. Findings showed that inclusion of 20% rice bran significantly (P<0.05) improved in total DMI than the other levels. A 30% RB inclusion was not able to improve further the total DMI, which might be due to the negative effect of higher level of anti-nutritional factor in rice bran. In-situ degradation of D3 and D4 recorded the higher estimated solid outflow rate indicating on the improvement on digestion of feedstuffs. The 20 and 30% RB inclusion resulted to significantly (p<0.05) higher OM digestibility of UTRS-based diet with Leucaena supplementation. ADG (41.1g), FCE (10.96) and benefit over feed cost Philippino Peso 238.2) was significantly higher in diet groups with 20% RB inclusion. Based on the results, it can be concluded that the supplementation of rice bran at 20% level is economic net income (US$ .040 /goat) in feeding goats with UTRS based diet and supplemented with 20% of Leucaena. Key words: goat; urea treated rice straw; rice bran; digestibility; growth performance DOI: 10.3126/njst.v9i0.3161 Nepal Journal of Science and Technology 9 (2008) 29-36